Integrating International Students Into Computer Science Programs: Challenges and Strategies for Success - Oudshoorn, MJ; Clear, A; Carter, J; Abandoh-Sam, JA; Gonsalvez, C; Hitchcock, L; Ittyipe, S; Mahadev, A; Pearce, JL (Association for Computing Machinery (ACM), 2017)
International students are an important and desirable constituent in most computer science programs. These students help to enrich the programs, bring new perspectives into the classroom, diversify the student population, globalize the curriculum, broaden the perspective of domestic students, and generate revenue for the host institution. Each of these characteristics is desirable and increasingly important in today's highly connected world and job market. Most institutions invest resources in attracting international students and provide orientation sessions for them on arrival to help acclimate them to the new environment and to introduce them to other students. There are often clubs to provide support groups and social functions to help them meet and make friends with domestic students. However, challenges for international students, and for the faculty teaching them, persist at many institutions despite these efforts to help international students deal with culture shock, differing academic expectations and teaching methods, and different attitudes toward issues such as plagiarism.